2019
DOI: 10.1007/s00500-019-04517-y
|View full text |Cite
|
Sign up to set email alerts
|

A hybrid combinatorial approach to a two-stage stochastic portfolio optimization model with uncertain asset prices

Abstract: Portfolio optimization is one of the most important problems in the finance field. The traditional mean-variance model has its drawbacks since it fails to take the market uncertainty into account. In this work, we investigate a two-stage stochastic portfolio optimization model with a comprehensive set of real world trading constraints in order to capture the market uncertainties in terms of future asset prices. Scenarios are generated to capture uncertain prices of assets. Stability tests are performed and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 100 publications
0
6
0
Order By: Relevance
“…The merits of this study utterly would be included as applying uncertain conditions, assessing various aspects of risk, and concentrating on economic criteria in the process of selection. ( Cui et al, 2020) suggested a two-stage stochastic portfolio optimization model with an extended set of real data trading constraints to tackle this issue regarding market uncertainty based on future asset price scenarios. In comparison to comprising models, it was concluded that the presented model is utterly reliable by employing the risk factors.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The merits of this study utterly would be included as applying uncertain conditions, assessing various aspects of risk, and concentrating on economic criteria in the process of selection. ( Cui et al, 2020) suggested a two-stage stochastic portfolio optimization model with an extended set of real data trading constraints to tackle this issue regarding market uncertainty based on future asset price scenarios. In comparison to comprising models, it was concluded that the presented model is utterly reliable by employing the risk factors.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The well‐known mean‐variance model of Markowitz (1952) was one of the pioneering efforts in this field, and up to now, it has been extended from different aspects (Mencarelli and D'Ambrosio, 2018). One of the important extensions of the Markowitz model is the incorporation of real‐world constraints such as cardinality and position size constraints and transaction costs (Lwin et al., 2017; Cui et al., 2020; Juszczuk et al., 2023). As pointed out by Lwin et al.…”
Section: Introductionmentioning
confidence: 99%
“…In this approach, the future price of assets is described as a finite set of scenarios, and the decision‐making process is divided into two stages. In the first stage, before any uncertainty realization, the portfolio selection is decided, and in the second stage, the return of the constructed portfolio is realized under each scenario (Cui et al., 2020). As mentioned earlier, although creating a portfolio with the maximum expected return is important, decision‐makers usually concern about the investment risk.…”
Section: Introductionmentioning
confidence: 99%
“…The paper by Zhang and Yang (2018) defines a new type of uncertain population growth model and uncertain logistic population growth model.The second category including seven papers applies uncertainty theory to solve various optimization problems. The two papers by andCui et al (2019) investigate different portfolio selection and optimization problems, respectively. The paper byChen and Zhu (2019) proposes an uncertain single period spatial oligopolistic electricity problem.…”
mentioning
confidence: 99%